Reducing prejudice and discrimination - Oskamp, Stuart (The Claremont Symposium on Applied Social Psychology, 2000)
Finding ways to reduce prejudice and discrimination is the central issue in attacking racism in our society. Yet this book is almost unique among scientific volumes in its focus on that goal. This combines critical analysis of theories about how to reduce prejudice and discrimination with cutting-edge empirical research conducted in real-world settings as well as in controlled laboratory situations. The authors in this volume focus on a common set of questions about ways to reduce intergroup conflict, prejudice, and stereotyping. Each contributor summarizes their own research as well as others' interprets the conclusions, and suggests implications concerning the practical methods that have been, or could be, used in programs aimed at reducing intergroup conflict. Ideal for teachers, social workers, administrators, managers, and other social practitioners who are concerned about prejudice and discrimination, this book will also serve as a valuable foundation of knowledge in courses that examine this topic.